Phononic Crystals Fundamentals and Applications - Khelif, Abdelkrim; Adibi, Ali.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2016)
This book provides an in-depth analysis as well as an overview of phononic crystals. This book discusses numerous techniques for the analysis of phononic crystals and covers, among other material, sonic and ultrasonic structures, hypersonic planar structures and their characterization, and novel applications of phononic crystals. This is an ideal book for those working with micro and nanotechnology, MEMS (microelectromechanical systems), and acoustic devices. This book also: Presents an introduction to the fundamentals and properties of phononic crystals Covers simulation techniques for the analysis of phononic crystals Discusses sonic and ultrasonic, hypersonic and planar, and three-dimensional phononic crystal structures Illustrates how phononic crystal structures are being deployed in communication systems and sensing systems.
Introduction to Acoustics of Phononic Crystals. Homogenization at Low Frequencies -- Fundamental properties of phononic crystal -- The Three-dimensional Phononic Crystals -- Computational Problems and Numerical Techniques for the Analysis of Phononic Crystals -- Phononic Crystal Membranes (Slabs or Plates) -- Surface Acoustic Waves in Phononic Crystals -- Optical characterization of phononic crystals in the time domain -- Optical Characterization of Phononic Crystals in the Frequency Domain -- Future Prospects of Phononic Crystals and Metamaterials.
Keywords: Microtechnology; Microelectromechanical systems; Optical materials; Lasers; Telecommunication; Microsystems and MEMS; Optical Materials; Laser; Microwaves, RF Engineering and Optical Communications